Preliminary Research Science and Islam Interactive Multimedia Based on Discovery Learning for Digital Era - Syefrinando, Boby; Ashyar, Rayandra; Sofyan, Sofyan; Wulandari, Bunga Ayu; Daulay, Hermalina (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of this study is to explain the preliminary research stage that was conducted at Jambi City Elementary School as preliminary data for research on the development of scientific and Islamic interactive multimedia based on discovery learning for digital era. The descriptive technique utilized in this study explains the preliminary research stage of the PLOMP development model. Interview guidelines and student digital literacy surveys were utilized as study instruments. According to the findings of the investigation, pupils’ digital literacy was in the good category, with percentages ranging between 62% and 65%. This implies that students can keep up with technical advancements in digital-era learning. This is an opportunity to create an ICT-based multimedia. This study will create scientific and Islamic interactive multimedia based on discovery learning to promote learning in the digital age while also exposing scientific principles and truths that are believed to exist in Islam.